Design and development of micro-electromechanical acoustic emission sensors - Pickwell, A. J. (Cranfield University, 2012)
Non-Destructive Testing (NDT) is a vital technique in modern engi- neering, enabling the monitoring of the structural health of a com- ponent and therefore enabling the prediction of component failure. Once the structural health of a component is known, timely main- tenance can be carried out to prevent component failure which may have resulted in costly downtime or injury. One NDT technique which has been of increasing interest over recent years is Acoustic Emission (AE) monitoring. AE monitoring technology has been successfully combined with preventative maintenance, saving millions of pounds worldwide. Cont/d.